Perancangan Platform Promosi dan Penjualan Home Industry Berbasis OpenCart di Padang Panjang - Janathan, Khalif; Annas, Firdaus; Annaufal, Hafizh (Yayasan Lembaga Studi Makwa, 2023)
Digital transformation is a challenge for MSMEs, especially in efforts to improve promotion and competitiveness in the digital era. This study aims to design an OpenCart-based e-commerce platform to support the promotion and sale of home industry products in Padang Panjang. This research method uses the Research and Development (R&D) methodology with the ADDIE development model, this study involves the stages of needs analysis, system design, implementation, and testing. This study identifies the main obstacles for MSME actors through surveys and interviews, including limitations in traditional promotion and digital access. The OpenChart framework was chosen because of its open-source, flexible, and easily customizable nature. This platform is also designed with features such as product catalogs, digital payment integration, promotion management systems, and comprehensive sales reporting. The test results show that the platform is able to increase operational efficiency in expanding market access to the national level. Users can feel the ease of managing products and promotions, while digital payment integration increases security in transactions. This shows that the OpenChart-based platform can be a strategic solution to overcome geographical constraints and increase the competitiveness of home industries. This research also provides real contributions in supporting the digitalization of MSMEs, strengthening the local economy, and creating new opportunities for small business actors to compete in a wider market.